A Contrastive Analysis towards English and Indonesian Noun Clauses - novalia tanasy (Universitas Lancang Kuning, 2022)
Main problem discussed in this study was the comparison of noun clauses in English and Bahasa Indonesia. The comparison aimed to find similarities and differences in the syntactic field that the noun clauses have in the two languages. This research applied contrastive analysis and the method was library research. The research instrument were noun clauses in English, Bahasa Indonesia and other linguistic issues especially books and internet citation supporting the main topic. The data analyzed by applying several theories in Content Analysis. This research found that English and Indonesian noun clauses cannot stand alone by themselves as sentences, they are introduced by conjunction and they need main clauses to produce sense. In terms of differences, English noun clause can function as objective complement but Indonesian noun clause cannot perform such function. English noun clause can be used as subject whereas Indonesian noun clause can be used as subject but introduced by any introductory words, the introductory word in English noun clause used as appositive cannot be omitted whereas the introductory word in Indonesian noun clause used as appositive can be omitted; the preposition in Indonesian noun clause used as object of preposition can be omitted whereas the preposition in English noun clause cannot be omitted.